Chlorophyll response to wind and terrestrial nitrate in the western and southern continental shelves of the Gulf of Mexico - González-Ramírez, Javier; Parés-Sierra, Alejandro; Cepeda-Morales, Jushiro (Frontiers in Marine Science, 2023)
In Mexico, 16 rivers directly discharge into the Gulf of Mexico. The Mexican rivers and those coming from the United States generate large regions in which phytoplanktonic primary production possesses a seasonal component that is linked to these nutrient-rich freshwater inputs. In the present study, new simulated flow and daily nutrient data were obtained for the largest Mexican rivers. These data were integrated as forcings in a configuration of the hydrodynamic Coastal and Regional Ocean COmmunity model coupled to an N2PZD2 biogeochemical model. We present a 21 year simulation using two different configurations. The first included river forcing, and the second did not consider their influence. The results were validated with satellite images of the surface chlorophyll concentration and discussed with data presented in previous studies. The model was able to realistically reproduce the seasonal dynamics of primary production in the Gulf of Mexico based on the concentration and distribution of chlorophyll, both at the surface and in the water column. We found significant differences in the response of chlorophyll to the input of nitrate from the rivers between both model configurations. The largest and most evident in the northern region of the continental shelf followed by the Bay of Campeche and Tamaulipas-Veracruz shelves. Finally, using the configuration with the river forcing, the physical processes that influence the dynamics of chlorophyll concentration in the deep region and continental shelf of the gulf were determined. In the deep region, primary production was driven by vertical mixing induced by the passage of cold fronts during winter and mesoscale structures. On the continental shelf, such dynamics were driven by coastal upwelling and fluvial nutrient contributions.